Physical Stability Test of Anti-Acne Cream from Ethanol Extract of Seruni Leaves (Spaghneticola trilobata) on Different Bases - Sari Wijayanti; Faizal Mustamin; Muhammad Luthfi (Jurnal FARMASIMED (JFM), 2025)
One of the formulations commonly used in treating acne is cream. However, most creams contain chemicals that can irritate the skin. Therefore, an alternative solution should be to use natural antibacterial ingredients. There is scientific evidence that chrysanthemum leaves (Spaghneticola Trilobata) have antimicrobial activity due to their secondary metabolite content consisting of terpenoids, flavonoids, steroids, tannins, saponins, and alkaloids. In this study, Chrysanthemum Leaf extract will be formulated into a physically stable anti-acne cream. To make chrysanthemum leaf ethanol extract cream, the concentration of stearic acid and TEA was varied. The amount of extract used to make the cream is 2.5%. Different concentrations of TEA:Stearic acid, namely F1 (0.2%:5%), F2 (0.4%:10%), and F3 (0.6%:15%). Type M/A cream that extracts ethanol from chrysanthemum leaves produces a semi-solid texture, olive green color, and characteristic odor of chrysanthemum leaves. After homogeneity test, the cream is said to be homogeneous because there are no coarse particles. The pH value of this cream is around 6-7, so it is safe to apply on the face. The spreadability test of Formula I, which reached 5.65 cm, met the standard for good cream spreadability, and the stickiness test, which lasted for 4.57 seconds, showed that this cream met the criteria for good stickiness. Formula I (F1) is the best formula that meets the criteria for a quality cream, according to the physical stability test results.